REPORT ON THE PRESIDENT. - Graham, Willard J. (The Accounting Review, 1956)
The author presents a report on the American Accounting Association activities based on a partly delivered speech by the president of the Association as of April 1956. The author provides statistics on member participation in the Association, mentioning that many members participate in more than one activity. He explains the activities of officers and committees with an example, highlighting the fact that each officer or committee views the Association primarily in terms of its field. He discusses the joint education committee and their chairmen, who considers his committee to be the most important and their achievements in their fields. The author throws light upon the representation of the Association by its president and other members and its cooperative relationship with other accounting organizations. He briefly mentions the annual conventions and annual reports in the journal "The Accounting Review." He also discusses the question of increasing membership for the Association.